The Degree Of the First three Grades Teachers Practice Of the Twenty-First Century Skills From Their Perspectives - Abu Hilal, Sawsan Ramzi Abdullah; Mansour, Othman Nasser (Journal of Educational and Psychological Sciences, 2023)
The study examined how female teachers of the first three grades implement twenty-first century skills from their perspectiv, A descriptive survey approch was used in the study, A questionnaire was developed for this purpose after it was verified to be valid and reliable, The study sample included (242) female teachers who were selected randomly. The study found that teachers of the first three grades practicing twenty-first century skills were highly rated. The results also showed that there were no statistically significant differences among the teachers of the first three grades practicing twenty-first century skills due to the variables: educational qualification, supervising authority, and years of experience. Study results recommended maintaining a high level of 21st century skills application.
Keywords: Thinking and problem-solving skills; digital and technological skills; life skills; classroom management; 21st century skills